Before Dred Scott - Twitty, Anne Silverwood, 1980- (New York, NY)
xiii, 285 sayfa
Keywords: “Before Dred Scott draws on the freedom suits filed in the St Louis Circuit Court to construct a groundbreaking history of slavery and legal culture within the American Confluence, a vast region where the Ohio, Mississippi, and Missouri Rivers converge. Formally divided between slave and free territories and states, the American Confluence was nevertheless a site where the borders between slavery and freedom, like the borders within the region itself, were fluid. Such ambiguity produced a radical indeterminacy of status, which, in turn, gave rise to a distinctive legal culture made manifest by the prosecution of hundreds of freedom suits, including the case that ultimately culminated in the landmark United States Supreme Court decision in Dred Scott vs Sandford. Challenging dominant trends in legal history, Before Dred Scott argues that this distinctive legal culture, above all, was defined by ordinary people's remarkable understanding of and appreciation for formal law.” --